Lacking measurement invariance in research self-efficacy: Bug or feature? - Klieme, Katrin Ellen; Schmidt-Borcherding, Florian (Frontiers in Education, 2023)
Psychological factors play an important role in higher education. With respect to students’ understanding of scientific research methods, research self-efficacy (RSE) has been studied as a core construct. However, findings on antecedents and outcomes of RSE are oftentimes heterogeneous regarding both its theoretical and empirical structure. The present study helps disentangle these findings by (a) establishing and validating an integrated, multi-dimensional assessment of RSE, and (b) introducing a developmental perspective on RSE by testing the impact of disciplinary context and academic seniority on both structure and level of RSE. Construct validity of the new measure was supported based on RSE assessments of 554 German psychology and educational science students. Relations to convergent and discriminant measures were as expected. Applying a developmental perspective on RSE, we expected differentiation of RSE latent structure based on disciplinary context and training level. Measurement invariance and LSEM analyses revealed respective differences in latent model parameters between most sub-groups. Considering our findings of measurement non-invariance as a feature rather than a bug, we propose a process-oriented theory of RSE structure and development. We discuss potential future directions of research and theory development that arise from our results alongside implications for methods education practice in higher education.